2013
DOI: 10.1158/1541-7786.mcr-13-0187
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Inhibition Induces Proinflammatory Cytokines via NOX4 in HNSCC

Abstract: Chronic inflammation plays a significant role in tumor promotion, migration and invasion. Using microarray analysis, we observed a profound increase in genes involved in pro-inflammatory pathways in epidermal growth factor receptor inhibitor (EGFRI)-treated head and neck squamous cell carcinoma (HNSCC) cell lines compared to their respective vehicle-treated cell lines. We hypothesized that the efficacy of EGFRIs may be offset by the pro-inflammatory response that these drugs produce in HNSCC tumor cells. We fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 38 publications
7
53
1
1
Order By: Relevance
“…In diseases characterized by sterile inflammation, such as cancer, elevated serum IL-6 levels indeed may be a surrogate for increased IL-1 signaling(31). At the level of the tumor microenvironment, increases in IL-6 production also occur secondary to EGFR blockade(32,33), which further feeds the cycle of immunosuppression due to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In diseases characterized by sterile inflammation, such as cancer, elevated serum IL-6 levels indeed may be a surrogate for increased IL-1 signaling(31). At the level of the tumor microenvironment, increases in IL-6 production also occur secondary to EGFR blockade(32,33), which further feeds the cycle of immunosuppression due to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated the reversal of HLA class I and APM component deficiency in HNC using the STAT1 agonist IFNγ, which enhanced CTL-mediated lysis and induced a higher level of peptide:HLA class I complexes (6,1114). EGFR antagonism can also increase expression of HLA class I expression (14,15) and pro-inflammatory cytokines (16). We have recently shown that SHP2, which operates downstream of EGFR and dephosphorylates p-STAT1, plays an important role in HLA-induced immune escape in HNC (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that erlotinib caused only minimal effects on the plasma Mg levels during earlier weeks of exposure (< 3 weeks) suggested that EGFR inhibition by erlotinib may not be the only mechanism causing Mg wasting in later weeks. Erlotinib is also known to activate NOX4 (8,9), the NADPH oxidase that is highly enriched in the kidney (23, 24). Thus, chronic erlotinib treatment may lead to activation of kidney NOX4 to generate H 2 O 2 ; it was previously demonstrated that H 2 O 2 alone can cause dose-dependent inhibition of TRPM6 channel activity and subsequently decreased re-absorption of Mg (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, preclinical in vitro patch clamp analyses in TRPM6-expressing renal cells showed that a physiological concentration (0.3 μM) of erlotinib did not inhibit EGF-induced changes in TRPM6 current density and tyrosine phosphorylation of EGFR (7). Erlotinib can provoke cellular oxidative stress in cancer cells through NOX-4 up-regulation (8 9…”
Section: Introductionmentioning
confidence: 99%